Trimetazidine Modulates Mitochondrial Redox Status and Disrupted Glutamate Homeostasis in a Rat Model of Epilepsy - Al-Shorbagy, Muhammad Y.; Wadie, Walaa; El-Tanbouly, Dalia M. (Frontiers in Pharmacology, 2021)
Mitochondrial oxidative status exerts an important role in modulating glia-neuron interplay during epileptogenesis. Trimetazidine (TMZ), a well-known anti-ischemic drug, has shown promising potential against a wide range of neurodegenerative disorders including epilepsy. Nevertheless, the exact mechanistic rationale behind its anti-seizure potential has not been fully elucidated yet. Herein, the impact of TMZ against mitochondrial oxidative damage as well as glutamate homeostasis disruption in the hippocampus was investigated in rats with lithium/pilocarpine (Li/PIL) seizures. Animals received 3 mEq/kg i.p. LiCl3 followed by PIL (single i.p.; 150 mg/kg) 20 h later for induction of seizures with or without TMZ pretreatment (25 mg/kg; i.p.) for 5 consecutive days. Seizure score as well as seizure latency were observed. Mitochondrial redox status as well as ATP and uncoupling protein 2 (UCP2) were recorded. Moreover, glutamate homeostasis was unveiled. The present findings demonstrated that the TMZ attenuated Li/PIL seizure score and latency. It improved mitochondrial redox status, preserved energy production mechanisms and decreased reactive astrocytes evidenced as decreased glial fibrillary acidic protein immune-stained areas in hippocampal tissue. Additionally, it modulated phosphorylated extracellular signal-regulated kinases (p-ERK1/2) and p-AMP-activated protein kinase (p-AMPK) signaling pathways to reflect a verified anti-apoptotic effect. Consequently, it upregulated mRNA expression of astroglial glutamate transporters and reduced the elevated glutamate level. The current study demonstrates that TMZ exhibited robust anti-seizure and neuroprotective potentials. These effects were associated with its ability to modulate mitochondrial redox status, to boost p-ERK1/2 and p-AMPK signaling pathways and to restore glutamate homeostasis in hippocampus.